Solid Oxide Fuel Cell (SOFC); A New Approach of Energy Generation during the Pandemic COVID-19 - Afroze, Shammya; Reza, Md Sumon; Cheok, Quentin; Taweeku, Juntakan; Azad, Abul K. (International Journal of Integrated Engineering, 2020)
The new coronavirus (COVID-19) has started spreading all over the world. Every infected is fighting to recover a little and every health worker is fighting to save a single life in this pandemic. There is no place for patients to stay in the hospital, health workers are given all possible services to save their lives. In this situation, uninterrupted power system is needed, which can be supplied by solid oxide fuel cells (SOFCs). Therefore, solid oxide fuel cells (SOFCs) are becoming attractive day by day with competing environmental friendly energy sources due to high energy efficiency, low emission rate and comparatively low operating cost. The purpose of this work is to investigate how copper-doped perovskite electrode materials impact the performance of solid oxide fuel cells (SOFCs) to overcome such crucial times successfully. Different synthesis process of Cu-based electrodes and analyzing electrochemical properties were investigated in this work. The evaluation were performed in terms of synthesis process, sintering temperature, lattice type and parameters, electrical conductivity, thermal expansion coefficients (TEC), polarization resistance, activation energy, and power density. In order to provide additional energy during this pandemic COVID-19, low-cost, highly performed, and durable materials are needed to make SOFC.